Student Expectations and Competencies in the Digital Library Learning/DILL Master Programme - Virkus, Sirje (Qualitative and Quantitative Methods in Libraries, 2017)
This paper presents the selected results of the survey of the students‟ expectations and competencies in the Digital Library Learning/DILL Master Programme during the period 2007-2013. Since 2007 a diagnostic analysis (DA) survey was conducted among DILL students before they started their studies in Tallinn University. The goal of the DA survey was to clarify the needs and expectations of the learners for the Information and Knowledge Management (IKM) and Human Resource Management (HRM) modules with regard to the content and delivery options. It was expected that it would enable to tailor the IKM and HRM modules in the best way to suit students‟ requirements within the framework that had been set.